Analyzing The Impact of Profitability, Dividend Policy, and Corporate Social Responsibility Disclosure on Firm Value - Ni Putu Eka Adnyani; I Gusti Ngurah Agung Suaryana (E-Jurnal Akuntansi, 2026)
This study aims to provide empirical evidence on the effects of profitability, dividend policy, and corporate social responsibility (CSR) disclosure on firm value. A purposive sampling method was used to select the sample, resulting in 45 data points collected from 2020 to 2022. The analysis was conducted using multiple linear regression with SPSS version 26. The findings indicate that dividend policy and profitability have a positive impact on firm value, while CSR disclosure has no significant effect. These results align with signaling theory, which suggests that dividend policy and profitability positively influence firm value.